2011
DOI: 10.1186/1471-2458-11-561
|View full text |Cite
|
Sign up to set email alerts
|

Sibling number and prevalence of allergic disorders in pregnant Japanese women: baseline data from the Kyushu Okinawa Maternal and Child Health Study

Abstract: BackgroundAlthough an inverse relationship between number of siblings and likelihood of allergic disorders has been shown in many epidemiological studies, the biological mechanism underlying this phenomenon has not yet been identified. There is no epidemiological research regarding the sibling effect on allergic disorders in Japanese adults. The current cross-sectional study examined the relationship between number of siblings and prevalence of allergic disorders among adult women in Japan.MethodsSubjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…There is increasing need for the improvement of socio economic conditions of dwellers in the sub-Sahara Africa and emission control of air pollutant. We did not find sibship, and pets, as an important association factor for the development of any of the allergic conditions as found by Miyake et al, [19,33].…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…There is increasing need for the improvement of socio economic conditions of dwellers in the sub-Sahara Africa and emission control of air pollutant. We did not find sibship, and pets, as an important association factor for the development of any of the allergic conditions as found by Miyake et al, [19,33].…”
Section: Discussionsupporting
confidence: 47%
“…Only few prevalence surveys have been conducted on allergic disorders among the adults' populations [19][20][21][22][23]. None of the few African studies examine the changes in the symptoms of allergic disorders in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 The risk of developing allergy was significantly associated with family history of the same in this study and several other studies. 2,[29][30][31] Studies have also observed that this increased risk seemed to be present no matter whichever type of allergic diseases were in family members indicating strong genetic component irrespective of varying prevalence and environmental risk factors of allergies in different societies. 4,32 These genetic factors form the non-modifiable factors in causation of allergies which cannot be controlled.…”
Section: Discussionmentioning
confidence: 99%